2021
DOI: 10.1186/s42269-021-00492-3
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and estimated genetic divergence times of banana cultivars (Musa spp.) from Java Island by maturase K (matK) genes

Abstract: Background The identification of banana cultivars genome is needed to provide a valid identity from the accession of bananas which are used as basic data in the management of in situ and ex situ banana conservation as well as for further breeding of banana cultivars. Results The size of PCR-amplified matK ranged from 844 to 860 bp and showed a high variability. The haplotype diversity was 0.9048 with nine haplotypes. Haplotype distribution map reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…The banana contained three genera (Musa, Musella, and Ensete) belonging to the Musaceae family. In addition, Musa acuminata and Musella balbisiana are the edible bananas [2,3]. Medicinal applications of banana peel products are getting greater attention from food manufacturers by transforming them into functional food.…”
Section: Introductionmentioning
confidence: 99%
“…The banana contained three genera (Musa, Musella, and Ensete) belonging to the Musaceae family. In addition, Musa acuminata and Musella balbisiana are the edible bananas [2,3]. Medicinal applications of banana peel products are getting greater attention from food manufacturers by transforming them into functional food.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed similar findings by Hand et al (2012) and Abouseada et al (2023). Studies by Probojati et al (2021), for instance, showed that the high nucleotide density among sequences of the matK gene is due to a large population historically. Along with this, findings reported by Viswanathan et al (2015), Nguyen et al (2019) and Yang et al (2023) suggest the effectiveness of matK gene-based primers in genetic diversity studies.…”
Section: Discussionmentioning
confidence: 99%
“…Grouping of cashew germplasm by specific molecular markers based on gene-based markers and DNA sequence has proven to be efficient and accurate when compared to morphometric techniques and other dominant markers (Wahyudi and Rifliyah, 2020; Probojati et al ., 2021). In cashew, maturase K ( mat K) is a chloroplast protein-coding gene of about 1547 bp.…”
Section: Introductionmentioning
confidence: 99%
“…Musa paradisiaca, generally known as banana, is a well-known tropical herbaceous plant of the Musaceae family (Probojati et al, 2021) and a major source of food all over the world (Yusoff, 2008). The banana is considered as a dessert cultivar, but the plantain is known as a culinary cultivar (Oyeyinka and Afolayan, 2020; Vu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%